Paulus retro? - Engberg-Pedersen, Troels (Dansk Teologisk Tidsskrift, 2012)
The article discusses claims made in a recent Danish book entitled Paul Plus – Four Prisms on Paul: Paul & Paul, & the Jews, & Luther, & Nietzsche (ed. Anna Vind; Copenhagen: Publications of the Faculty of Theology 30, 2012). Against the contributors, who are basically presenting a traditional, Lutheran understanding of Paul in opposition to the ‘New Perspective on Paul’, it is fi rst argued that not only was Paul a Jew: he also continued to see himself as a Jew and took the new Christ faith to be an eminently Jewish phenomenon; and secondly that a number of further features of a ‘New Perspective’ on Paul (he speaks ethnically about Jews and Gentiles, not about human beings vis-à-vis God; and he envisages an actual fulfi llment of the Mosaic Law among Christ believers, not a continued state of being simultaneously ‘justifi ed and a sinner’) follow directly from the fi rst basic feature.